Joaquim Nogueira, práticas de leituras no Instituto de Humanidades de Fortaleza, edições escolares e a cultura cearense nas três primeiras décadas do Século XX - Silva, Ana Glória Lopes da (2010)
The thesis results of research on the books dealing with the culture of Ceará for the basic school, in Ceará in the first three decades of the twentieth century. For this purpose, came from experiences and scholarly editions produced by Joaquim Nogueira and used by teachers and students of the Institute of Humanities. During this period, the director, later known as Colégio Nogueira, publishing several editions of didactic as Baralho Aritmético, Lições progressivas de primeiras letras, Jornal Bandeirantes, Revista Escolar and the book reading Anno Escolar. The constitution of meanings, practices, strategies of appropriation and editor to write and keep their issues is the problem that emerges both through analysis of readings from the students and the organization of the book Anno Escolar. The cultural history of books and reading, especially the contributions of Roger Chartier, Michel de Certeau, Daniel Fabre, Alain Choppin, Anne-Marie Chartier and Jean Hébrard, inspired by the work of building theoretical and methodological approach. The productions of the brazilian historiography of books and reading, like the works of Tania Regina de Luca, Arlette Medeiros Gasparello and Circe Maria Bittencourt, are also needed for this work and approach. The sources used are the Livro de Partes do Colégio Nogueira, the book Vida Escolar do Colégio Nogueira, the Revista Escolar do Instituto de Humanidades, the book Anno Escolar do Instituto de Humanidades, the Jornal do Ceará, among others.